2019
DOI: 10.1080/08998280.2019.1593725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of melanoma incidence in metropolitan areas versus nonmetropolitan areas in the state of Texas stratified by poverty classification

Abstract: Numerous risk factors for the development of melanoma have been identified; however, there is conflicting research on whether residence in nonmetropolitan areas, with a population <49,999 people, is associated with an increased cancer risk. This retrospective study aimed to identify the correlation of nonmetropolitan residence in Texas and the incidence of melanoma, while also stratifying the results by poverty level. Data were obtained from the Texas Department of State Health Services' Texas Cancer Registry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, a study by Azhar et al in Texas, which has the largest rural population in the US, showed that the proportion of residents with melanoma in nonmetropolitan areas was 1.39 times higher than in metropolitan areas between 1996 and 2015. 26 The substantial growth in the incidence of LM/LMM in rural areas observed in our study reflects the ongoing improvement in comprehensive data collection and increased access to primary care physicians and dermatologists in rural areas.…”
Section: Discussionmentioning
confidence: 51%
“…However, a study by Azhar et al in Texas, which has the largest rural population in the US, showed that the proportion of residents with melanoma in nonmetropolitan areas was 1.39 times higher than in metropolitan areas between 1996 and 2015. 26 The substantial growth in the incidence of LM/LMM in rural areas observed in our study reflects the ongoing improvement in comprehensive data collection and increased access to primary care physicians and dermatologists in rural areas.…”
Section: Discussionmentioning
confidence: 51%